2016
DOI: 10.1111/cgf.12887
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Bar Chart Authoring with Microsoft Excel and Tangible Tiles

Abstract: Providing tools that make visualization authoring accessible to visualization non-experts is a major research challenge. Currently the most common approach to generating a visualization is to use software that quickly and automatically produces visualizations based on templates. However, it has recently been suggested that constructing a visualization with tangible tiles may be a more accessible method, especially for people without visualization expertise. There is still much to be learned about the differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 24 publications
1
40
0
Order By: Relevance
“…Many participants also made use of the "Show me" pane to explore alternative visualization types, however, we observed this type of exploration much less frequently than in the classroom context of the pilot study. These notable differences in the sequence of actions confirm the results of previous studies that compared approaches of constructing bar charts using template-based digital tools and physical tiles [44].…”
Section: Data Attributes Identificationsupporting
confidence: 86%
See 1 more Smart Citation
“…Many participants also made use of the "Show me" pane to explore alternative visualization types, however, we observed this type of exploration much less frequently than in the classroom context of the pilot study. These notable differences in the sequence of actions confirm the results of previous studies that compared approaches of constructing bar charts using template-based digital tools and physical tiles [44].…”
Section: Data Attributes Identificationsupporting
confidence: 86%
“…Wun et al [44] compared building bar charts using MS Excel vs. a set of physical tiles. They found that the building process was very different for the two tools.…”
Section: Previous Empirical Findingsmentioning
confidence: 99%
“…Previous studies exist that have investigated the visualization process using different tools (e.g., [WPHC16,MHN17,GTS10,Hur14]). For example, Wu et al [WPHC16] compared the bar chart construction process between MS Excel and a set of physical tiles. Their findings showed that the distribution of time spent and sequence of actions taken to construct visualizations are different depending on the tool.…”
Section: Previous Studies Of Visualization Constructionmentioning
confidence: 99%
“…Their findings showed that the distribution of time spent and sequence of actions taken to construct visualizations are different depending on the tool. Unlike the study by Wu et al [WPHC16], we investigate trade-offs of visualization construction in digital visualization tools. In another study, Mendez et al…”
Section: Previous Studies Of Visualization Constructionmentioning
confidence: 99%
“…Additionally, the question arises in which ways physical and digital visualizations can be combined and complement each other. An example would be choosing to perceive data through a specific modality and switching in between tasks, depending on the comfort, speed or facility the data can be explored in the individual modality (e.g., Wun et al [2016]). …”
Section: Interacting With Physicalizationsmentioning
confidence: 99%